INSTRUMENTOS PARA LA VIDA, OFRENDAS PARA LA MUERTE: UN ESTUDIO DEL AJUAR FUNERARIO WARI DE HUACA PUCLLANA - Paz Flores, Gladys (2017)
During the last years of Huaca Pucllana Project of Research, Conservation and Re-Valuation (PICPVHP), directed by Dr. Isabel Flores Espinoza, the Wari funerary contexts found on top of the Great Pyramid have become the main focus of study. There, several elements were found on the site in good state of preservation, such as structures, funerary bundles and offerings. The present article deals with these offerings and their study, and it suggests a typology inside the Wari funerary objects, which provide us information about the people who were buried there and the participants during the funerary ritual, according to their position, specific features and contents. All of this takes into consideration the analysis of bone remains, fabric and vegetal tissue by the Project’s specialists. These analysis are done in order to obtain results that will help us with the discussion of this topic and further interpretations.